Reducing physical restraints by older adults in home care: development of an evidence-based guideline - Scheepmans, Kristien (BMC Geriatr, 2020)
BACKGROUND: Restraint use is a complex and challenging issue in home care. Due to socio-demographic trends, worldwide home healthcare providers are faced with an increasing demand for restraint use from informal caregivers, patients and healthcare providers, resulting in the use of various types of restraints in home care. Awareness and knowledge of restraint use in home care, its implications and the ethical challenges surrounding it are of crucial importance to its reduction. This research aimed to describe the development process of an evidence-based practice guideline to support caregivers to optimize home care. METHOD: The practice guideline was developed according to the framework of the Belgian Centre for Evidence-Based Medicine and AGREE II. The guideline was developed over several stages: (1) determination of the target population and scope, (2) literature search, (3) drafting and (4) validation. A multidisciplinary working group determined the proposed purpose, target group, and six clinical questions for the guideline. A consensus procedure and consultation by experts were used to develop the guideline. RESULTS: The guideline provides an answer to six clinical questions and contains ten key recommendations based on the classification of GRADE, with the objective of increasing healthcare providers’ awareness, knowledge and competence to adequately deal with situations or questions related to restraint use. The guideline also includes a flowchart for dealing with complex situations where the use of restraints is requested, already present or considered. CONCLUSIONS: The guideline was validated by the Belgian Centre for Evidence-Based Medicine. Increasing competence, awareness and knowledge related to restraint use are key objectives of the guideline for reducing restraint use in home care. A multicomponent intervention to support healthcare workers in implementing the guideline in clinical practice needs to be developed.